The terminology of the macaxeira: constitution of a corpus - Oliveira, Simone Cordeiro de [UNESP]; Babini, Maurizio [UNESP] (Red Iberoamericana Terminologia-riterm, 2016)
Cassava (Monihot spp.) is one of the most important agricultural commodities in Brazil, and then in Acre state is the one that contributes among cultures of continuation income support. The main aim of this article is to demonstrate a methodological framework used to establish a terminological and monolingual corpus of cassava in Acre state of Brazil named as TERMacax-AC. In order to achieve this study, the theoretical principles was focused on Terminology concerning the debate on Aubert (2001), Krieger (2001), Krieger e Finatto (2004), Barros (2004, 2007); and also on Corpus Linguistics following the discussions from Berber Sardinha (2004), Almeida e Correia (2008) e Orenha-Ottaiano (2009). The first phase of this study was the configuration of a corpus from the project: contextual identification and definition of the objectives. Moreover, it was carried on a research of the resources, choosing the ones according to the criteria established. After that, the data was collected, cured, organization of the texts and the presentation of the TERMacax-AC arrangement. At the end, it was carried on the analysis and discussion of the significant points of this study. Currently, TERMacax-AC covers at about 1.000.000 words and will support the implementation of the Onomasiological Dictionary of Fundamentals Terms of Cassava.
Keywords: cassava; cassava terminology; monolingual and terminological corpus; TERMacax-AC